Heutagogy Theory as an Approach to Implementing Inclusive Education in Higher Education: A Bibliometric Analysis - Jatiningsiwi, Tata Gading; Ediyanto, Ediyanto; Kawai, Norimune (Jurnal Pendidikan Bitara UPSI, 2024)
Explorations in the implementation of learning models in inclusive education settings continue to be studied. However, many approaches remain under-examined, including heutagogy theory. The purpose of this study is to examine heutagogy theory as it relates to inclusive education in higher education. This study is a preliminary study for needs analysis. The method used was bibliometric analysis. The procedures used in conducting bibliometric analysis are: defining the purpose and scope of the bibliometric study, selecting techniques for bibliometric analysis, collecting data for bibliometric analysis, and conducting bibliometric analysis and reporting results. The study results show that there is not much research on the application of heutagogy theory in inclusive education in higher education. Therefore, there are still many opportunities to analyze the theoretical basis of heutagogy to inclusion in higher education. So, further research is needed on the strategies to be undertaken to apply heutagogy theory to implement academic inclusion in higher education through the design of learning models.